(untitled) (Analysis in Theory and Applications, 2011)
In this note, we prove that the Toeplitz-type Operator Θ_α^b generated by the generalized fractional integral, Calderón-Zygmund operator and VMO function is bounded from L^p,λ (R^n) to L^q,μ (R^n). We also show that under some conditions Θ_α^b f V L^q,μ (B_R), the vanishing-Morrey space.